(untitled) (Jurnal Pengelolaan Lingkungan Pertambangan, 2025)
Gold mining activities play a significant role in Indonesia’s economy but also present challenges such as land degradation and environmental pollution. Reclamation efforts are crucial to restore ecological function and soil productivity in former mining areas. This study analyzed the effects of reclamation and revegetation on soil fertility in former gold mining areas managed by PT Tambang Tondano Nusajaya (PT TTN) and PT Meares Soputan Mining (PT MSM) in North Minahasa. Soil samples were collected from revegetated areas aged 2–10 years and compared with undisturbed forest soils. Physical properties (texture, bulk density, porosity) and chemical properties (pH, organic C, total N, total P, available P, cation exchange capacity (CEC), and base saturation) were analyzed. The results showed that the soils in revegetated areas had low to moderate bulk density and porosity values, and their chemical properties were characterized by very low to low organic C and total N, low to high CEC, and very high base saturation. Soil texture with dominant proportions of sand remained unchanged due to its permanent feature. Despite ongoing revegetation, the fertility of soils in reclaimed areas remained below undisturbed forest soils, with no significant improvements observed over the revegetation period. These findings emphasize the need for additional soil ameliorants to enhance soil quality and fertility in mine reclamation